2015
DOI: 10.2527/jas.2015-9243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pilot-scale microencapsulation of probiotics and product effect on broilers1

Abstract: This study was conducted to evaluate the pilot-scale production of microencapsulated in a 500-L fermenter using emulsion and gelation and to assess the effect of the products on the growth performance, antioxidant activity, immune function, and cecal microbiota in Arbor Acres broilers. A total of seven hundred 1-d-old male Arbor Acres broilers were randomly assigned to 7 dietary treatments with 5 replicate pens per treatment and 20 broilers per pen. The dietary treatments were as follows: 1) basal diet (CON), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…Two tested probiotic strains, including S. boulardii (CGMCC No. 10381) (Zhang et al 2015a, b) and E. faecium (CGMCC No. 2516) (Zhang et al 2015a, b), were cultured under microencapsulated and free non-encapsulated conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Two tested probiotic strains, including S. boulardii (CGMCC No. 10381) (Zhang et al 2015a, b) and E. faecium (CGMCC No. 2516) (Zhang et al 2015a, b), were cultured under microencapsulated and free non-encapsulated conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Zhang et al. ( 2015 ) a total of 700 one‐day‐old Arbor Acres chickens for fattening were allocated to seven dietary treatments and distributed in five pens per treatment, in groups of 20 birds per each pen. Two basal diets based on maize and soybean meal (starter days 1−21 and grower days 22−42) were either not supplemented (control) or supplemented with different treatments.…”
Section: Assessmentmentioning
confidence: 99%
“…The two studies in laying hens showed that dietary chlortetracycline supplementation did not affect laying performance of hens (Uuganbatar et al., 2005, 500 mg chlortetracycline/kg feed; Zhang et al., 2015 , 1,000 mg chlortetracycline/kg feed).…”
Section: Assessmentmentioning
confidence: 99%
“…Cabe indicar que esta estrategia de encapsulación se ha venido utilizado con otras moléculas y se han encontrado resultados eficientes; una de ellas es el zinc, donde a dosis de 100 ppm con una cubierta lipídica del 10 %, se pueden mitigar los síntomas de colibacilosis en cerdos destetados (96) ; además, diferentes estudios han demostrado que el uso de cultivos probióticos en forma protegida es una estrategia viable para mejorar la digestibilidad y absorción de nutrientes, mejorar el sistema inmunológico y prevenir infecciones en especies tanto rumiantes como monogástricos (97,98,99) . Por lo tanto, el diseño de sistemas de encapsulación de AH puede ser una estrategia cercana a implementarse con fines zootécnicos y con lo que podrá esclarecerse la ruta de acción y los efectos que estos compuestos pueden ocasionar.…”
Section: Biodisponibilidad De áCidos Hidroxicinámicosunclassified